1996
DOI: 10.1046/j.1365-2265.1996.8560864.x
|View full text |Cite
|
Sign up to set email alerts
|

Size at birth and adrenocortical function in childhood

Abstract: These findings suggests that the intra-uterine environment, as measured by fetal size at birth, has long-lasting effects on the function of the hypothalamo-pituitary-adrenal axis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
129
3
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(141 citation statements)
references
References 21 publications
8
129
3
1
Order By: Relevance
“…Differences in HPA activity among our study groups also may reflect conditions of gestation and subsequent development that could contribute to variation in HPA activity. For instance, chronically stressed Dominican children exhibited low unstressed levels of cortisol (Flinn & England, 1995), orphanage-reared Romanian children exhibit altered HPA activity (Gunnar, Morison, Chisholm, & Schuder, 2001), and gestational stress has been associated with increased HPA reactivity in children (Clark et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in HPA activity among our study groups also may reflect conditions of gestation and subsequent development that could contribute to variation in HPA activity. For instance, chronically stressed Dominican children exhibited low unstressed levels of cortisol (Flinn & England, 1995), orphanage-reared Romanian children exhibit altered HPA activity (Gunnar, Morison, Chisholm, & Schuder, 2001), and gestational stress has been associated with increased HPA reactivity in children (Clark et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Our data are in agreement with Waddell et al who reported increased adrenal expression of the ACTH-R in 6-month-old offspring and increased stress-induced levels of plasma corticosterone in a rat model of programming in which dams received dexamthasone during gestation. 18 In humans, low birth weight is associated with increased urinary glucocorticoid excretion in children 57 and with elevated basal plasma cortisol concentration 58 and greater adrenocortical responsiveness to ACTH in adults. 59 This increased responsiveness to stress has been proposed to contribute to the pathogenesis of chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…High birth weight may be positively associated with childhood (152) and adolescent height (153). However, estrogen and androgen concentrations seem elevated in prepubescent children who had lower birth weights, independent of current weight (154,155), and data consistently indicate that menarche is earlier in these girls (152,153,(156)(157)(158). In fact, epidemiologic data seem to indicate that the association of high birth weight with breast cancer risk in premenopausal women is not likely to be mediated through height, weight, or growth velocity in childhood and adolescence (159,160), but possibly through greater adult height (161).…”
Section: Prenatal Risk Factors For Breast Cancer Cancer Epidemiol Biomentioning
confidence: 99%